Hyperechogenicity of the Substantia Nigra in Parkinson’s Disease: Insights from Two Brothers with Markedly Different Disease Durations - Julie M. Hall; Matthew J. Georgiades; Deborah A. Hammond; Xiaoting Feng; Ahmed A. Moustafa; Simon J. G. Lewis; Gabrielle Todd (Case Reports in Neurological Medicine)
We present clinical features and substantia nigra morphology for two brothers with Parkinson’s disease (PD) aged 60 and 59 years. The brothers were diagnosed at 41 and 50 years of age, respectively. Both patients exhibited an abnormally large area of substantia nigra echogenicity bilaterally when viewed with transcranial ultrasound. The abnormality was similar in both brothers despite one having a much longer disease duration than the other. These findings further highlight that transcranial ultrasound is not associated with severity of clinical symptoms, but it might assist in the diagnosis of PD provided that it is combined with other variables known to precede PD.